Investigation of the Projector Properties of the Magnetic lenses Using Analytical Function - Al-Batat, A. H.H.; Yaseen, M. J.; Majeed, M.M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A computational investigation has been carried out to describe synthesis optimization procedure of magnetic lenses. The research is concentrated on the determination of the inverse design of the symmetrical double polepiece magnetic lenses whose magnetic field distribution is already defined. Magnetic lenses field model well known in electron optics have been used as the axial magnetic field distribution. This field has been studied when the halfwidth is variable and the maximum magnetic flux density is kept constant. The importance of this research lies in the possibility of using the present synthesis optimization procedure for finding the polepieces design of symmetrical double polepiece magnetic lenses which have the best projector focal properties.